2015
DOI: 10.1155/2015/301029
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Extract ofZingiber officinaleandZea mays(Purple Color) Improves Neuropathy, Oxidative Stress, and Axon Density in Streptozotocin Induced Diabetic Rats

Abstract: Based on the protective effect of the combined extract of purple waxy corn and ginger (PWCG) on oxidative stress related disorders in diabetic condition, we aimed to determine the effect of PWCG on the functional, biochemical, and structural change of the lesion nerve in streptozotocin- (STZ-) diabetic rats. PWCG at doses of 100, 200, and 300 mg·kg−1 BW were orally given to STZ-diabetic rats which were subjected to chronic constriction (CCI) at right sciatic nerve for 21 days. The blood sugar was assessed befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…In agreement with previous studies, we showed that diabetic neuropathic pain is accompanied by an increased level of mRNA expression of GFAP and CD11b [34]- [36]. We noted a decrease in the expression of GFAP and CD11b by ECF.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies, we showed that diabetic neuropathic pain is accompanied by an increased level of mRNA expression of GFAP and CD11b [34]- [36]. We noted a decrease in the expression of GFAP and CD11b by ECF.…”
Section: Discussionsupporting
confidence: 93%
“…In STZ-induced Sprague Dawley rats, the combined administration of honey (2 g/kg body weight) and ginger (60 mg/kg body weight) for three weeks significantly ( p < 0.05) reduced the superoxide dismutase and catalase activities and the malondialdehyde levels, whereas the reduced glutathione level and the reduced glutathione/oxidized glutathione ratio were significantly elevated ( p < 0.05) [ 129 ]. In STZ-induced diabetic rats, oral administration with the combined extract of purple waxy corn and ginger at doses of 100, 200, and 300 mg/kg body weight for 21 days improved chronic constriction at the right sciatic nerve by improving the oxidative stress status and the axon density in the lesion nerve [ 130 ]. Ginger was also found to inhibit α -glucosidase and α -amylase enzymes, which is useful for T2DM management, and inhibition of COX was observed, which protects against inflammation [ 131 ].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Thus, early DN may be cured by RHL; however, if glomerulosclerosis and interstitial fibrosis had been present, DN would have hardly been cured. Oxidative stress has been reported to be responsible for the development of peripheral diabetic neuropathy ( 20 , 21 ). MDA, SOD and GSH-px are indicators of the oxidative stress status ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%